Spatial Resolution Analysis for Few-Views Discrete Tomography Based on MART-AP Algorithm. (23rd January 2013) - Konovalov, Alexander B.; Vlasov, Vitaly V.
Abstract : We study a new MART-AP algorithm of few-views discrete tomography. Its efficiency for high-frequency structure reproduction is investigated in a numerical experiment where we reconstruct a 2D model for the estimation of the spatial resolution limit. We estimate the modulation transfer function of the reconstruction algorithm and compare it with the modulation transfer function of projection distortions. Our results show that MART-AP weakly influences the contrast of spatial structures being reproduced and can be used for high-resolution reconstruction when only a few projections are registered.